Linking Supply Chain Strength to Sustainable Development and Innovation: A Country-Level Analysis - Lin, Pei-Jung (2009)
The study ascertained the presence of association between supply chain efficiency and sustainable development together with innovation within a country. This study determined as well the link that bonds supply chain efficiency with environmental performance. The study clarified that supply chain efficiency affects corporate environmental processes by any means. Lastly, the study evaluated how supply chain efficiency affects social sustainability and sustainable development. The main task for gathering data was to put together all the archives of the Global Competitiveness Report and Environmental Performance Index Reports, spanning from 2005 to 2008. The Pearson Product Moment Correlation Coefficient has been computed to ascertain if there are significant bivariate relationships between the variables of interest. Sustainable development means fulfilling the present generations needs without compromising the needs of future generations. This just proved that human needs are important. Thus, it presented that sustainability relies on economic development that involves a country’s population. This also reflects that the environment has limitations in assimilating the effects of human activities (Kates et al, 2005). Environmental limitations refer to continuous effects of human activities with the use of resources and elements provided by nature, and the Earth’s capabilities of accumulating wastes and emissions (Clift 2003). Both sustainable development and innovation are significantly and positively correlated with supply chain efficiency.